HDAC4 mutant represses chondrocyte hypertrophy by locating in the nucleus and attenuates disease progression of posttraumatic osteoarthritis - Xiaodong Gu; Fei Li; Yangyang Gao; Xianda Che; Pengcui Li (BMC Musculoskeletal Disorders, 2022)
Abstract Background The aim of this study was to evaluate whether histone deacetylase 4 S246/467/632A mutant (m-HDAC4) has enhanced function at histone deacetylase 4 (HDAC4) to attenuate cartilage degeneration in a rat model of osteoarthritis (OA). Methods Chondrocytes were infected with Ad-m-HDAC4-GFP or Ad-HDAC4-GFP for 24 h, incubated with interleukin-1β (IL-1β 10 ng/mL) for 24 h, and then measured by RT-qPCR. Male Sprague-Dawley rats (n = 48) were randomly divided into four groups and transduced with different vectors: ACLT/Ad-GFP, ACLT/Ad-HDAC4-GFP, ACLT/Ad-m-HDAC4-GFP, and sham/Ad-GFP. All rats received intra-articular injections 48 h after the operation and every 3 weeks thereafter. Cartilage damage was assessed using radiography and Safranin O staining and quantified using the OARSI score. The hypertrophic and anabolic molecules were detected by immunohistochemistry and RT-qPCR. Results M-HDAC4 decreased the expression levels of Runx-2, Mmp-13, and Col 10a1, but increased the levels of Col 2a1 and ACAN more effectively than HDAC4 in the IL-1β-induced chondrocyte OA model; upregulation of HDAC4 and m-HDAC4 in the rat OA model suppressed Runx-2 and MMP-13 production, and enhanced Col 2a1 and ACAN synthesis. Stronger Safranin O staining was detected in rats treated with m-HDAC4 than in those treated with HDAC4. The resulting OARSI scores were lower in the Ad-m-HDAC4 group (5.80 ± 0.45) than in the Ad-HDAC4 group (9.67 ± 1.83, P = 0.045). The OARSI scores were highest in rat knees that underwent ACLT treated with Ad-GFP control adenovirus vector (14.93 ± 2.14, P = 0.019 compared with Ad-HDAC4 group; P = 0.003 compared with Ad-m-HDAC4 group). Lower Runx-2 and MMP-13 production, and stronger Col 2a1 and ACAN synthesis were detected in rats treated with m-HDAC4 than in those treated with HDAC4. Conclusions M-HDAC4 repressed chondrocyte hypertrophy and induced chondrocyte anabolism in the nucleus. M-HDAC4 was more effective in attenuating articular cartilage damage than HDAC4.